A Comparison of Automobile Insurance Regimes in Canada - Devlin, Rose (Assurances et gestion des risques / Insurance and Risk Management, 2019)
This article compares and contrasts automobile insurance provisions across Canadian jurisdictions, with particular emphasis on comparing how British Columbia (BC) fares relative to other provinces. A brief discussion of the different automobile insurance regimes is provided, as well as the mandated packages in each province. Price quotes are obtained by jurisdiction for the mandated package as well as for enhanced packages, for a hypothetical driver (either male of female) with a driving record that is good or poor, who is 45 years of age and drives a Honda Civic. We find that prices in Vancouver, BC are in the middle of the pack, and are much lower than in Toronto, Ontario for a driver with a good record. BC average prices are similar to those in Saskatchewan and Manitoba. Loss ratios vary quite a bit over the period 2011-2015, with no clear pattern except that they are always higher in public regimes than private ones. Because these ratios fluctuate from year to year, no one single province has performed consistently or significantly better than the others. One must be very careful when drawing hard and fast conclusions because of the differences in insurance packages across provinces and the aggregated and limited nature of much of the available data. Four conclusions are notable: (i) Automobile prices charged in BC are in line with those of Manitoba, (ii) a driver in Vancouver pays significantly less than an otherwise comparable driver in Toronto, (iii) in the private system, Ontario has the lowest loss ratios while, in the public system, there is no discernable, stable, relationship across the jurisdictions, and (iv) average claim costs cannot be compared across regimes.